Influence of the concentration of Sb2O3 on the electrical properties of SnO2 varistors - Ciórcero, J.R.; Pianaro, S. A.; Bacci, G.; Zara, Alfredo José; Tebcherani, S. M.; Longo, Elson [UNESP] (Springer Nature, 2011)
Varistors are electronic materials with nonohmic behavior. In traditional SnO2 varistors, CoO acts as a densifying agent, Nb2O5 increases the electrical conductivity of SnO2 grains, and Cr2O3 produces a more uniform microstructure and acts as an oxygen retaining agent at the grain boundaries. The present work involved a systematic study of the substitution of Nb2O5 for Sb2O3 in the composition of a ternary varistor system. The compositions were prepared by conventional wet ceramic processing using deionized water, and the resulting slips were dried by spray-drying. Pellets were produced under a pressure of 330 MPa and sintered at 1,350 °C for 2 h. Similar to the behavior of Nb2O5, increasing the concentration of Sb2O3 reduced the nonlinear behavior of the ceramic and its breakdown electric field while increasing its leakage current. The samples’ microstructure showed greater porosity, suggesting that higher concentrations of Sb2O3 reduce the sintering rate, probably in response to the higher concentration of tin vacancies in the structure.